2015
DOI: 10.1111/ddi.12399
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater fishes of China: species richness, endemism, threatened species and conservation

Abstract: Aim To compile an inventory of freshwater fish species in China, and to investigate these data to determine spatial patterns in species richness, endemism and threatened species for the purpose of facilitating conservation. Location China Methods Literature, databases and fish collections were examined to create an inventory database of freshwater fishes of China. This list was analysed to determine species richness, endemism and threatened species. spss and origin software were used to determine relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Currently, 20% of finfishes with highest aquaculture production (> 25 000 t year À1 ) are foreign to China and some dominate present-day fish communities in southern China (Wang et al, 2014;Xing et al, 2015). Additionally, we found that translocated species are also the important contributor to future homogenization, highlighting the urgent need to better understand the geographic routes of domestic translocations and identifying management strategies for reducing secondary spread.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Currently, 20% of finfishes with highest aquaculture production (> 25 000 t year À1 ) are foreign to China and some dominate present-day fish communities in southern China (Wang et al, 2014;Xing et al, 2015). Additionally, we found that translocated species are also the important contributor to future homogenization, highlighting the urgent need to better understand the geographic routes of domestic translocations and identifying management strategies for reducing secondary spread.…”
Section: Discussionmentioning
confidence: 83%
“…However, due to intensifying economic growth, China is currently facing a biodiversity crisis of unparalleled magnitude (Xie et al, 2001;Liu & Diamond, 2005). Freshwater fish are among the most imperilled taxa, threatened by dam construction, land degradation and water pollution (Kang et al, 2013b;Xing et al, 2015). Freshwater fish are among the most imperilled taxa, threatened by dam construction, land degradation and water pollution (Kang et al, 2013b;Xing et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There have been over 1300 freshwater fish species listed in China (Xing et al, 2016). The present study revealed that a total of 154 freshwater fish species (138 native and 16 non-native species), belonging to 10 orders, 31 families and 104 genera are found on Hainan Island.…”
Section: Fish Biodiversity and Conservationmentioning
confidence: 62%
“…They cover less than 1% of the earth's surface, yet support over 10% of the species (Strayer and Dudgeon, 2010) and are regarded to be in a state of crisis (Vörösmarty et al, 2010),with higher proportion of species threatened with extinction here than in their terrestrial and marine counterparts (Strayer and Dudgeon, 2010).The main threats to freshwater biodiversity include: overexploitation, water pollution, flow modification, habitat degradation, and non-native species (Dudgeon et al, 2006). Consistent with other regions of China, inland fisheries are an important threat to the freshwater fish of Hainan Island (Xing et al, 2016). In 2014, the freshwater fisheries of Hainan harvested 22 073 tons, which is 15 times more than that of 26 years earlier.…”
Section: Threats To Freshwater Fish Biodiversitymentioning
confidence: 96%
See 1 more Smart Citation